Perinatal systemic gene delivery using adeno-associated viral vectors - Karda, Rajvinder; Buckley, Suzanne M. K.; Mattar, Citra N.; Ng, Joanne; Massaro, Giulia; Hughes, Michael P.; Kurian, Manju A.; Baruteau, Julien; Gissen, Paul; Chan, Jerry K. Y.; Bacchelli, Chiara; Waddington, Simon N.; et al. (Frontiers in Molecular Neuroscience, 2014)
Neurodegenerative monogenic diseases can also affect a broad range of tissues and organs throughout the body. An effective treatment would require a systemic approach. The intravenous administration of novel therapies is ideal but is hampered by the inability of such drugs to cross the blood-brain barrier and precludes efficacy in the central nervous system. A number of these early lethal intractable diseases also present devastating irreversible pathology at birth or soon after. Therefore, any therapy would ideally be administered during the perinatal period to prevent, stop or ameliorate disease progression. The concept of perinatal gene therapy has moved a step further towards being a feasible approach to treating such disorders. This has primarily been driven by the recent discoveries that particular serotypes of adeno-associated virus (AAV) gene delivery vectors have the ability to cross the blood-brain barrier following intravenous administration. Furthermore, this has been safely demonstrated in perinatal mice and non-human primates. This review focuses on the progress made in using AAV to achieve systemic transduction and what this means for developing perinatal gene therapy for early lethal neurodegenerative diseases.